Análise da demonstração do fluxo de caixa e seus indicadores em companhias representativas no espaço aéreo brasileiro - Almeida, Regina Santos (2016)
The publication of the Law 11.638/2007, replaces the statement of sources and uses of funds by the statement of cash flows (DFC). At first the research presents the concept, the objectives of financial statements with a greater emphasis on the statement of cash flow, the research object, with its components from operating activities, investing and financing, the development of methods of demonstration we discuss the cash flow and demonstrates the viability of the financial analysis based on DFC were calculated and interpreted the extracted quotients of reports published by companies available on the Anac website, Azul Airlines, Avianca Brazil, Gol Linhas Aereas and TAM Airlines, for two consecutive years of 2014 and 2013. the indexes are classified into four categories: 1st category quotients box cover, 2nd quotients category of quality of the result, 3rd quotients category Capital expenditures and 4th category returns of cash flows, whose purpose varies the evaluation of the enterprise liquidity to determine the cash return rates